THE MONTESSORI APPROACH TO PARENTING FOR CREATING A SUSTAINABLE LEARNING ENVIRONTMENT FOR GENERATION ALPHA - Siti Maryatul Kiptiyah; Puji Yanti Fauziah; Chandra Anggyetta Pramesti (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2025)
Generation Alpha is growing up in a complex and fast-changing digital age, demanding an adaptive, holistic and sustainability-orientated parenting approach. Ecologically-conscious Montessori parenting comes as a strategy that unites concrete experiential learning with the development of social, emotional and environmental values. This article aims to examine how this approach can create a sustainable learning environment for Alpha Generation children. The study was conducted through a literature review method of academic and relevant sources. The results show that Montessori parenting supports children's character building through structured learning environments, strengthening agency, and reflective observation from parents. This approach contributes to parenting that aligns children's developmental needs with global challenges, and strengthens the sustainability of education within the family, community, and global society.